Natural Nanoparticles, Anthropogenic Nanoparticles, Where Is the Frontier? - Lespes, Gaëtane; Faucher, Stéphane; Slaveykova, Vera I. (Frontiers in Environmental Science, 2020)
Nano-sized particles are important components of the Earth biogeochemical system. However, in the Anthropocene, the human activities disturbed their natural cycle and increased their abundance by (i) affecting their emissions and releases; (ii) altering the environmental processes involving nanoparticles; and (iii) introducing anthropogenic nanoparticles. Intentionally or unintentionally released, the occurrence of the anthropogenic particles in the environment is continuously rising. Both natural and anthropogenic nanoparticles are recognized as important carriers for trace elements and organic micropollutants and key modifiers of their transport, speciation, bioavailability and effects in the environment. Nevertheless, currently they are considered separately, despite the necessity of more integrated, broader and non-sectorial perspective taking together particles of different origins and various processes likely to generate and involve them. The present paper provides a perspective on the environmental processes involving anthropogenic and natural nanoparticles; discusses the role of human activities in nanoparticle cycling, as well as the necessity to bridge the divide between the natural and anthropogenic nanoparticles. The discussion will be supported by the examples of our own research to ask, if there is still a frontier between natural and anthropogenic nanoparticles?